Estimands in a Chronic Pain Trial: Challenges and Opportunities. (2nd January 2020) - Callegari, Francesca; Akacha, Mouna; Quarg, Peter; Pandhi, Shaloo; von Raison, Florian; Zuber, Emmanuel
Abstract: An estimand clearly defines the target treatment effect to be estimated in a clinical trial. A recently published draft International Conference on Harmonization E9 addendum introduces the concept of estimand in clinical trials and provides a structured framework to link trial objectives, design, conduct, statistical analysis, and interpretation in a coherent way. In the meantime, regulators are already keen to discuss the definition of estimands for new clinical trials. In this manuscript, we focus on the primary clinical question of interest and on the corresponding estimand specification for a future Phase 2 study in chronic pain. This entails, in particular, the identification and handling of intercurrent events relevant in the chronic pain field. The primary estimand with its detailed rationale for consideration is presented, together with the primary estimation method. Other supplementary estimands are also defined to assess slightly different treatment effects. Some practical considerations arising from the development of the estimand concept for this trial are summarized, outlining the challenges encountered, how these have been overcome and the opportunities discovered during this process.